Potensi Peninggalan Arkeologi Benteng Orange di Gorontalo Utara sebagai Sumber Belajar Sejarah Lokal - Arrazaq, Naufal Raffi; Tasnur, Irvan; Rumambie, Wira Pratama (Universitas Pendidikan Indonesia, MSI, dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2025)
Orange Fort in North Gorontalo is an archaeological heritage site with significant historical value, yet its potential as a learning resource has not been fully explored. This study aims to analyze the potential of Orange Fort as a source for local history learning and to formulate appropriate strategies for its integration into history education at the senior high school level. This research employs a literature review method by collecting and examining relevant sources on historical heritage, history pedagogy, and cultural site utilization. The collected data were then analyzed to determine the relevance of the fort’s historical content to the history curriculum and its possible applications in classroom practice. The findings reveal that Orange Fort holds strong potential as a local history learning resource and can be integrated into various pedagogical approaches, such as field trips, digital learning media development, and student research projects. Utilizing the fort as a learning source not only enriches historical content but also enhances students’ historical awareness, critical thinking skills, and sense of nationalism. Furthermore, the sustainable use of this site requires proper conservation and management efforts. Therefore, collaboration among government agencies, educators, academics, and local communities is essential to preserve and develop Orange Fort as a meaningful and sustainable educational resource for local history learning. This study contributes to the discourse on place-based history education and highlights the importance of integrating cultural heritage sites into the formal curriculum. Abstrak Orange Fort di Gorontalo Utara merupakan tinggalan arkeologis yang memiliki nilai historis penting dan berpotensi besar untuk dimanfaatkan sebagai sumber pembelajaran sejarah lokal. Namun, pemanfaatannya dalam konteks pendidikan masih belum optimal. Penelitian ini bertujuan untuk menganalisis potensi Orange Fort sebagai sumber belajar sejarah lokal serta merumuskan strategi pemanfaatannya dalam pembelajaran sejarah di sekolah menengah. Penelitian ini menggunakan metode studi pustaka dengan menghimpun berbagai literatur mengenai sejarah benteng, pembelajaran sejarah, dan pemanfaatan situs budaya. Data yang diperoleh dianalisis untuk mengkaji relevansi konten sejarah benteng dengan kurikulum sejarah serta bentuk implementasinya dalam proses pembelajaran. Hasil penelitian menunjukkan bahwa Orange Fort dapat dijadikan sumber belajar melalui berbagai model pembelajaran, seperti kunjungan lapangan (field trip), pengembangan media digital berbasis situs sejarah, dan proyek penelitian siswa. Pemanfaatan benteng sebagai sumber belajar tidak hanya memperkaya materi sejarah lokal, tetapi juga meningkatkan kesadaran sejarah, keterampilan berpikir kritis, serta menumbuhkan rasa nasionalisme siswa. Selain itu, pemanfaatan situs memerlukan strategi pelestarian dan pengelolaan yang tepat agar keberlanjutannya terjaga. Oleh karena itu, kolaborasi antara pemerintah, pendidik, akademisi, dan masyarakat sangat diperlukan untuk menjadikan Orange Fort sebagai sumber belajar sejarah lokal yang edukatif, kontekstual, dan berkelanjutan.